Immune dysfunction in patients with end-stage chronic renal failure - U. A. Dostiev; A. R. Dostiev; A. M. Karimov (Трансплантология (Москва), 2016)
This literature review presents an immune system disorder in end-stage renal disease (ESRD), emphasizing the specific role of uremia and related changes. Finally, on the basis of new relationships between the changes in the immune system of ESRD patients, it emphasizes the potential role of the immune dysfunction as the main cause of the highmortality in this patient population and the need for further research in this area.